Age-Related Decline in Disengaging Spatial Attention in Physiological Aging - Tiziana Pedale; Serena Mastroberardino; Nicola Tambasco; Valerio Santangelo (Brain Sciences)
Background/Objectives: Attention is a complex process involving various components such as alerting, orienting, and resolving conflicts. These components have been widely examined using the Attention Network Test (ANT), which has also been used to explore attentional decline associated with aging. However, discrepancies exist in the literature regarding which specific aspects of attention are most impacted by aging. These inconsistencies could be due to methodological issues such as group comparisons that may exaggerate differences between groups while flattening subtle variations within groups. Methods: To address this issue, we administered the ANT to 60 healthy participants aged between 62 and 90 years. Using a multivariate regression analysis, we examined whether increasing age was associated with changes in alerting, orienting, and conflict resolution, while controlling for overall performance in terms of both reaction times and accuracy. Results: The results showed a general and age-insensitive decline in two of the three attentional components: the alerting effect, which was abolished, and a large conflict effect, which was present regardless of age. In contrast, the orienting of spatial attention was found to linearly increase with increasing age. More focused analyses revealed that the ability to shift attention from the central (initial) to the peripheral (target) location slowed down as a function of age. Conclusions: These results suggest that aging is associated with a greater difficulty in disengaging endogenous attention from the central, uninformative cue to direct attention on task-relevant peripheral targets.